Draft Annual Plan 2006-2007 Volume-II (Tables) Government of Rajasthan - Planning Commission (Planning Commission, 2006)
Draft annual plan 2006-07 proposed outlay- financial summary Draft annual plan 2006-07 proposed outlay - schemewise Physical target and achievements Externally aided projects- financial outlay Detail of IEBR of SLPEs Bharat nirman programmes Draft annual plan 2006-007 outlays- by head of development - for district plans Centrally sponsored schemes- financial outlays schemewise Draft annual 2006-07 special moment plan for scheduled castes (SCP) Draft annual 2006-07- roads and bridges- targets & achievements.
Government of Rajasthan Planning Department